Representasi Patriarki dalam Film “Barbie” (2023) Karya Greta Gerwig - She Radyan Alya Monica Anandira (INDO PUBLISHING, 2026)
Patriarchy remains a social system that influences gender relations and is frequently represented through mass media, including films. Greta Gerwig's Barbie (2023) presents a critique of patriarchy through its narrative, dialogues, and character interactions, portraying gender inequality and the construction of power within society. This study aims to analyze the representation of patriarchy in Barbie (2023) using Sara Mills' Critical Discourse Analysis by examining the positions of subject, object, and audience in constructing meaning within the discourse. This research employs a critical paradigm with a qualitative approach. Data were collected through observation of Barbie (2023), documentation, and literature review, and were analyzed based on Sara Mills' concepts of subject position, object position, and audience position. The findings indicate that Barbie (2023) represents patriarchy as a social construct operating through power relations, the construction of gender identity, and the normalization of values that place women in subordinate positions. Furthermore, the film positions its audience to critically interpret patriarchy through satire, irony, and conflicts among the characters. Therefore, Sara Mills' Critical Discourse Analysis effectively reveals how patriarchal ideology is represented and simultaneously challenged through the film's narrative.